Measurement of Floating Potential and Ion Concentration in Arc Plasma at Atmospheric Pressure - Jha, V. K.; Mishra, L. N.; Narayan, B. (Journal of Nepal Physical Society, 2020)
Arc plasma is generated using low voltage dc power supply for the measurement of plasma parameters such as floating potential and ion-concentration in the plasma seeded with molybdenum. Langmuir moving probe is used in order to measure the probe current at different values of the dc potential applied on the probe. A graph is plotted between the probe current and the probe potential, based on data at the atmospheric pressure, using the experimental set up in the gas discharge chamber for the single probe method. The floating potential is calculated to be 32V, and the average ion-concentration to be 1.43 - 10e16m3.